Correction: Chronological reassessment of the Middle to Upper Paleolithic transition and Early Upper Paleolithic cultures in Cantabrian Spain - Marín-Arroyo, Ana B.; Rios-Garaizar, Joseba; Straus, Lawrence G.; Jones, Jennifer R.; de la Rasilla, Marco; González Morales, Manuel R.; Richards, Michael; Altuna, Jesús; Mariezkurrena, Koro; Ocio, David (PLOS ONE, 2018)
null